To Understand Inequity, Bioethics Needs to Sort Things Out - Cho, Mildred K. (The Hastings Center report, 2023)
Bioethics is reexamining how to implement diversity, equity, inclusion, and justice concerns into scholarship. However, bioethicists should question the categories used to define diversity. The act of categorization is value laden, and classification systems confer power and benefits and generate harms. For example, what conditions count as disabilities? We should consider the equity implications of offering only “male” and “female” options for self-identification in health records. However, we should also interrogate all ideas about categorization, including how categories are formed, why they are formed, and who decides. Bioethicists cannot comprehend fully what equity and justice mean for underrepresented, underserved, or marginalized people until there is an understanding of how the boundaries of marginalization are created.